2021
DOI: 10.30987/2658-4026-2021-1-27-35
|View full text |Cite
|
Sign up to set email alerts
|

Improving the cognitive clarity of graph models of knowledge representation and decision-making using visualization

Abstract: The article discusses the ways to improve the cognitive clarity of graph models for knowledge representation and decision making by applying visualization capabilities. Using fuzzy cognitive models as an example, it is shown that applying an approach based on visualization metaphors allows one to structure and partially formalize the task of increasing the cognitive clarity of models, breaking it down into separate easily interpreted stages, each of which contributes to providing cognitive clarity in general. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In [11][12][13][14], the authors investigated aspects of application of visualization metaphors in the problems of visualization of fuzzy cognitive maps and graph models in general. Summarizing the results obtained, the process of visualizing a graph model using a visualization metaphor can be represented as a diagram in Fig.…”
Section: Visualization Metaphors As a Means Of Increasing Cognitive Clarity Of Graph Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11][12][13][14], the authors investigated aspects of application of visualization metaphors in the problems of visualization of fuzzy cognitive maps and graph models in general. Summarizing the results obtained, the process of visualizing a graph model using a visualization metaphor can be represented as a diagram in Fig.…”
Section: Visualization Metaphors As a Means Of Increasing Cognitive Clarity Of Graph Modelsmentioning
confidence: 99%
“…In [14] using an example of visualization of fuzzy cognitive maps, the authors showed that use of visualization metaphors allows structuring and partially formalizing the task of increasing cognitive clarity of a visual representation. They also hypothesized that a similar effect can be achieved through the use of visualization metaphors for graph models of other types.…”
Section: Fig 1 Graph Model Visualization Using a Metaphormentioning
confidence: 99%
“…In [11][12][13][14], the authors investigated aspects of application of visualization metaphors in the problems of visualization of fuzzy cognitive maps and graph models in general. Summarizing the results obtained, the process of visualizing a graph model using a visualization metaphor can be represented as a diagram in Fig.…”
Section: Visualization Metaphors As a Means Of Increasing Cognitive Clarity Of Graph Modelsmentioning
confidence: 99%
“…In [14], the authors, using an example of visualization of fuzzy cognitive maps, showed that use of visualization metaphors allows structuring and partially formalizing the task of increasing cognitive clarity of a visual representation. They also hypothesized that a similar effect can be achieved through the use of visualization metaphors for graph models of other types.…”
Section: Visualization Metaphors As a Means Of Increasing Cognitive Clarity Of Graph Modelsmentioning
confidence: 99%